Library preservation in Russia: hope and despair on the edge of the technological revolution - Popova‐Gosart, Ulia (Library Management, 2004)
The paper discusses the state of library preservation as the main problem of library management in Russia during the times of transition to digital environments. Today, Russia's extensive library system is undergoing a paradigm change toward the implementation of information technology (IT) to develop public access to information, that is perceived to be vital for the growth of the country. The first principal projects to elevate Russia to the ranks of the technologically advanced started as recently as 1990s, and, although having had some success, the country's digital resources remain grossly inadequate to support the growing public demand for information and education. Despite its state of retardation, the problems of preserving digital sources in Russia are evident to concerned specialists in the fields of informational science and archive work. Although these and other related problems are not addressed widely enough, they have gradually surfaced as an undeniable priority for the international preservation community. There is a promise to continue the necessary training and education that will link the national Russian library system with more collaborative projects and with leading international organizations. © 2004, Emerald Group Publishing Limited. All rights reserved.
Keywords: Digital storage; Libraries; Russia; dept.ils

Managing the information revolution: library management, the control of prescriptive technologies, and the future of librarianship - Sierpe, Eino (Library Management, 2004)
This article seeks to promote a critical perspective on the present conceptualization of library management and the problems posed by technology. More specifically, it addresses the challenges faced by library administrators in relation to computing technologies. Through the adoption of Ursula Franklin's view of technology as “practice”, the article contrasts the practice of holistic and prescriptive technologies in library contexts. It also addresses the transformations of librarianship and the increasing adoption of prescriptive technological models. To exemplify the ongoing destruction of traditional librarianship, the three practices that comprise the fundamentals of librarianship are analyzed, namely, cataloging, collection development, and reference work. © 2004, Emerald Group Publishing Limited
Keywords: Information management; Librarianship; Libraries; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils

Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils